Investigation on temporal evolution of the grain refinement in copper under high strain rate loading via in-situ synchrotron measurement and predictive modeling. (15th January 2018) - Shah, Pooja Nitin; Shin, Yung C.; Sun, Tao
Abstract: Synchrotron X-rays are integrated with a modified Kolsky tension bar to conduct in situ characterization of the grain refinement mechanism operating during the dynamic deformation of metals. Copper with an initial average grain size of 36 μm is refined to 6.3 μm when loaded at a constant high strain rate of 1200 s −1 . Synchrotron measurements revealed the temporal evolution of the grain refinement mechanism in terms of the initiation and rate of refinement throughout the loading test. A multiscale finite element based recrystallization model has been developed to predict the grain size evolution occurring during the dynamic deformation process. The model accurately predicts the initiation and temporal evolution of the refinement phenomenon with a predicted final average grain size of 2.4 μm. Graphical abstract: Image 1